1994
DOI: 10.3758/bf03209159
|View full text |Cite
|
Sign up to set email alerts
|

Latent inhibition as a performance deficit resulting from CS—context associations

Abstract: Treatments that attenuate latent inhibition (U) were examined using conditioned suppression in rats. In Experiment 1, retarded conditioned responding was produced by nonreinforced exposure to the CS prior to the CS-US pairings used to assess retardation (Le., conventional U). In Experiment la, retarded conditioned responding was induced by preexposure to pairings of the CS and a weak US prior to retardation-test pairings of the CS with a strong US (Le., Hall-Pearce [1979] U). Both types of U were attenuated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
95
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 23 publications
10
95
1
1
Order By: Relevance
“…(2) Long retention intervals between training and testing have produced attenuation ofextinction (Pavlov, 1927) and the CS preexposure effect (Kraemer, Randall, & Carbary, 1991). (3) Posttraining extinction manipulations have successfully revealed latent associations in the CS preexposure effect (Grahame, Barnet, Gunther, & Miller, 1994) and the US preexposure effect (Matzel, Brown, & Miller, 1987). (4) Second-order conditioning procedures have been observed to promote the expression of otherwise unexpressed learning in simultaneous conditioning (Barnet, Arnold, & Miller, 1991;Rescorla, 1980) and trace conditioning deficits (Cole, Barnet, & Miller, 1995b).…”
Section: Resultsmentioning
confidence: 99%
“…(2) Long retention intervals between training and testing have produced attenuation ofextinction (Pavlov, 1927) and the CS preexposure effect (Kraemer, Randall, & Carbary, 1991). (3) Posttraining extinction manipulations have successfully revealed latent associations in the CS preexposure effect (Grahame, Barnet, Gunther, & Miller, 1994) and the US preexposure effect (Matzel, Brown, & Miller, 1987). (4) Second-order conditioning procedures have been observed to promote the expression of otherwise unexpressed learning in simultaneous conditioning (Barnet, Arnold, & Miller, 1991;Rescorla, 1980) and trace conditioning deficits (Cole, Barnet, & Miller, 1995b).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the latent inhibition effect can be disrupted by presentation of the US in a different context (Kaspow, Catterson, Schachtman & Miller, 1984), the passage of time between Phase 1 (pre-exposure) and Phase 2 (CS-US training; e.g., Kraemer, Randall & Carbary, 1991, Hall & Minor, 1984 and 'extinction' of the context present in Phase 1 (Baker & Mercier, 1982;Grahame, Barnet, Gunther, & Miller, 1994; but see also, Hall & Minor, 1984;Zalstein-Orda & Lubow, 1995).…”
Section: Deconstructing Latent Inhibitionmentioning
confidence: 99%
“…On the other hand, there are numerous studies, using fear conditioning in rats, that have shown that overshadowing of one element (A) ofa reinforced AB compound can be reversed by posttraining extinction of B (Kaufman & Bolles, 1981;Matzel, Schachtman, & Miller, 1985;Yin, Grahame, & Miller, 1993). Similarly, latent inhibition ofa CS was attenuated by extensive exposure to the training context (i.e., context extinction) following CS-US pairings (Grahame, Barnet, Gunther, & Miller, 1994). However, in several other studies in which rats were trained with an AB compound followed by extinction of B, decreased performance to A was observed (e.g., Holland & Ross, 1981;Rescorla & Cunningham, 1978;Speers, Gillan, & Rescoria, 1980).…”
mentioning
confidence: 99%
“…Thus, the detection ofevidence for retroactive revaluation may depend on whether A borrows associative strength from B on test. For example, in several ofthe experiments by Miller and his colleagues (e.g., Grahame et a!., 1994;Yin et a!., 1993), retroactive revaluation of a discrete CS was brought about by extinction of the training context. In these experiments, the critical CS-context associations would have been relatively weak in comparison with the strong odor-taste associations established in the experiment reported by Durlach and Rescorla (1980).…”
mentioning
confidence: 99%